Growth and physiological response of rice ‘Inpari 35’ under salinity stress and application of silicate fertilizer - Aulia Noor Ramadhani; Diah Rachmawati (Biogenesis: Jurnal Ilmiah Biologi, 2021)
Rice is an important staple food in Indonesia. Crop areas can be expanded to boost productivity by utilizing marginal lands, which are saline. This study aims to study the growth and physiological response of rice ‘Inpari 35’ to the application of silicate fertilizer under salinity stress conditions. This study used a completely randomized design (CRD) with two factors. The first factor is the difference in NaCl salt concentration consisting of N0: 0 mM; N1: 37.5 mM; N2: 50 mM, while the second factor is the difference in the concentration of silicate fertilizer (CaSiO3) consisting of S0: 0 mM; S1: 1 mM and S2: 2 mM. Each treatment combination was repeated three times. Observed data were analyzed by analysis of variance (ANOVA). A significant difference between treatments is continued with Duncan's multiple distance test at a 95% confidence level. The results showed that NaCl treatment significantly (p<0.05) inhibited the growth of rice ‘Inpari 35’, which was indicated by a decrease in the plant height and number of leaves. The NaCl treatment caused a reduction in the levels of chlorophyll, carotenoids, proline, membrane stability index (MSI), and relative water content (RWC). The interaction between NaCl treatment and CaSiO3 showed significant differences in physiological parameters by increasing the levels of chlorophyll, carotenoid, proline, membrane stability index, and relative water content.